Improvement of Crisis Management in a Tourist Enterprise - Batorski, Jarema (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
Economic crises may impact the development of a crisis situation in tourist enterprises. It is assumed that tourism is one of the sectors most sensitive to economic fluctuations, and the tourist economy is especially threatened with those crises the sources of which have an external character. However, crisis situations in enterprises are caused by numerous and various factors generating crises, of both endogenous and exogenous character. On the other hand, enterprises’ crises have a significant meaning for developing the economic situation. The actual aid provided to managers dealing with an organizational crisis depends on the awareness of the anti-crisis management’s significance, and especially the problems they have to face. The aim of the article is to present methodology enabling increasing the ability of tourist enterprises to manage when in a crisis.